Caring for carers in Liaoning Province strengthening elderly workforce in the People Republic of China. - Noy, Ilan (ADB briefs., 2019)
The PRC has one of the fastest-growing elderly populations in the world. There is a significant gap between the demand for formal long-term care for the elderly and availability of supply in terms of services provided by nursing homes and institutions, particularly in rural areas such as Liaoning Province. This policy brief can guide future research on human resource development for elderly care as well as the creation of workforce education and training programs to ensure that long-term care institutions in the PRC can provide safe and high-quality services.